Retirement and healthcare utilization - Wolfgang Frimmel; Gerald Pruckner (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Pension systems and their reforms are often discussed in the context of financial viability. These debates grow in intensity with the aging of the population in industrialized countries. However, an increase in retirement age may create unintended side effects for retirees' health or healthcare costs. This paper empirically analyzes the effect of (early) retirement on individual inpatient and outpatient healthcare expenditure in Austria. We use comprehensive labor market and retirement data from the Austrian Social Security Database combined with detailed information about individual inpatient and outpatient healthcare service utilization for the province of Upper Austria. To account for the endogeneity in retirement decisions, we exploit exogenous variation in the early retirement age induced by two Austrian pension reforms in 2000 and 2003. We find significant negative effects of retirement on healthcare expenditure. For both sexes, retirement decreases subsequent expenditure for outpatient medical attendance and hospitalization. Analyses of disaggregated components of healthcare expenditure confirm a positive health effect caused by physical and emotional relief after retirement. Apart from direct health effects, the results also reveal behavioral changes in the utilization of healthcare services. These changes in health behavior seem in particular relevant for blue collar workers.
Keywords: I11; I12; J26; H51; 330; retirement; healthcare expenditure; health behavior; instrumental variable